North from Rome - MACINNES, HELEN; HELEN MACINNES (Connecticut Fawcett Publications, Inc, 1958)
a Cold War thriller following Bill Lammiter, an American playwright in Rome trying to win back his ex-fiancée.
Keywords: noisy living conditions in multi-story apartment complexes called insulae; characterized by greater frugality, sobriety, and traditional reverence compared to the capital